Analysis Mix Digital Marketing towards Satisfaction Customers in SMEs in Village Padang Tualang - Nurafrina Siregar (International Journal of Management, Economic and Accounting, 2023)
Digital marketing is promotional activities and market search through online digital media by utilizing various means such as social networks. The aim of this research is to increase knowledge and skills about digital marketing, especially social media, for Small and Medium Enterprises (SME) business people to increase their sales and profits. Technology currently continues to develop and the benefits of using the internet are felt by its users. Some people feel dependent on the internet, including the activities of Small and Medium Enterprises (SMEs) in utilizing information technology to run their business. The aim of this research is to generally describe the impact of digital marketing on SMEs. From the research results, it is known that digital marketing makes it easier for SMEs to provide information and interact directly with consumers, expand market share, increase awareness and increase sales for SMEs.